Comment on “Marxist view on global political economy and new market trends” - Cheng R., Cheng (2023)
Commented Article: ZHANG, Fengrong; XIAO, Qianwen. Marxist view on global political economy and new market trends. Trans/Form/Ação: Unesp journal of philosophy, v. 46, Special Issue, p. 79- 106, 2023.